2014
DOI: 10.1007/978-3-319-07440-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of User Age on Smartphone and Tablet Use, Measured with an Eye-Tracker via Fixation Duration, Scan-Path Duration, and Saccades Proportion

Abstract: Abstract. The design of user interfaces plays an important role in human computer interaction, especially for smartphones and tablet devices. It is very important to consider the interface design of smartphones for elderly people in order for them to benefit from the variety applications on such devices. The aim of this study is to investigate the effects of user age as well as screen size on smartphone/tablet use. We evaluated the usability of smartphone interfaces for three different age groups: elderly age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…The older group also focused on the face significantly more times. Although the average fixation duration on the bear’s face was not significantly different, several previous studies reported that older adults require longer fixation to perceive visual information than younger adults [ 82 , 83 ]. Additionally, they may not have had enough time to look at the other AOIs.…”
Section: Discussionmentioning
confidence: 80%
“…The older group also focused on the face significantly more times. Although the average fixation duration on the bear’s face was not significantly different, several previous studies reported that older adults require longer fixation to perceive visual information than younger adults [ 82 , 83 ]. Additionally, they may not have had enough time to look at the other AOIs.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies on screen size in Media Psychology and Human-Computer Interaction (Al-Showarah et al, 2014;Castellà et al, 2016;Maniar et al, 2008;Szarkowska, et al, 2015) suggested that larger screens provide a more satisfactory experience. Taking into account these studies, we put forward two hypotheses on the effects of screen size on subtitle layout preferences and comprehension: Hypothesis 1: viewers will evaluate subtitles differently depending on the screen size.…”
Section: Overview Of the Studymentioning
confidence: 99%
“…A number of studies in the fields of Media Psychology, and Human-Computer Interaction (Al-Showarah, AL-Jawad, and Sellahewa, 2014;Kim, Sundar, and Park, 2011;Lombard, Ditton, Grabe, and Reich, 1997;Maniar, Bennett, Hand, and Allan, 2008) have also focused their research of screen size on viewers' perception of mobility and content, and on attitudes towards technology. Lombard et al (1997) studied the role of screen size in small and large television screens.…”
Section: Screen Size Effects Across Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, younger participants, particularly children, appreciated the application more and the whole experience attracted and motivated them to interact and to acquire the knowledge in an indirect manner. Previous HCI studies on the effect of user age show that small screen sizes and complexity cause more difficulties for elderly people in browsing smartphone interfaces [Al-Showarah et al 2014]. Elderly people also may have decreased capabilities for interfaces that require motor actions of the neck and face [Hands and Stepp 2016].…”
Section: Age-related Differencesmentioning
confidence: 99%